2006
DOI: 10.1016/j.cplett.2006.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Energy of the quasi-free electron in xenon

Abstract: Field ionization of trimethylamine and of N,N-dimethylaniline doped into xenon is presented as a function of xenon number density up to the density of the triple point liquid, both at noncritical temperatures and along the critical isotherm. These data exhibit a decrease in the xenon induced shift of the dopant ionization energy near the xenon critical point. The energy of the quasi-free electron, arising from dopant field ionization, in xenon is calculated within a local Wigner-Seitz model to within ±0.3% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The Lennard-Jones parameters for the atomic fluids and the modified Stockmeyer parameters for the CH 3 I/Ar and CH 3 I/Kr interactions were identical to the parameters used to model accurately the perturber-induced shift of the dopant ionization energy for methyl iodide in argon [12][13][14]61], krypton [12,15,61] and xenon [16,61]. The parameters κ 0 , z 1 , z 2 , ε and σ in eq.…”
Section: Intermolecular Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lennard-Jones parameters for the atomic fluids and the modified Stockmeyer parameters for the CH 3 I/Ar and CH 3 I/Kr interactions were identical to the parameters used to model accurately the perturber-induced shift of the dopant ionization energy for methyl iodide in argon [12][13][14]61], krypton [12,15,61] and xenon [16,61]. The parameters κ 0 , z 1 , z 2 , ε and σ in eq.…”
Section: Intermolecular Potentialsmentioning
confidence: 99%
“…However, high-n Rydberg states are usually too sensitive to perturber density fluctuations, which makes these individual dopant states impossible to investigate. (Nevertheless, under the assumption that high-n Rydberg state energies behave similarly to the ionization threshold of the dopant, dopant high-n Rydberg state behavior in supercritical fluids can be probed indirectly by studying the energy of the quasi-free electron, through photoinjection [2][3][4][5][6][7][8][9][10][11] and field ionization [12][13][14][15][16][17][18][19].) Low-n Rydberg states, on the other hand, are excellent spectroscopic probes to investigate excited state/fluid interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As in our previous investigations [1][2][3][4][5][6][7][8][9], dopant photoionization spectra in Ne and He were measured with monochromatic synchrotron radiation having a resolution of 9 meV in the spectral region of interest. The copper sample cell is equipped with entrance and exit MgF 2 (or LiF) windows and a pair of parallel plate electrodes (stainless steel, 3.0 mm spacing) oriented parallel to the incoming radiation and perpendicular to the windows.…”
Section: Methodsmentioning
confidence: 99%
“…(2), g PD ðrÞ is the dopant/perturber radial distribution function and w þ ðrÞ is the dopant cation/perturber interaction potential. These studies [1,[3][4][5][6][7][8] showed that V 0 ðq P Þ was independent of temperature, except near the critical density along the critical isotherm of the perturber. This critical point effect led to the development of the local Wigner-Seitz model for V 0 ðq P Þ.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation